Effects of sorghum varieties on microbial communities and volatile compounds in the fermentation of light-flavor Baijiu - Tang, Jie; Lin, Bin; Shan, Yimin; Ruan, Song; Jiang, Wei; Li, Qun; Zhu, Liping; Li, Rui; Yang, Qiang; Du, Hai; Yang, Shengzhi; Sun, Qi; et al. (Frontiers in Microbiology, 2024)
Light-flavor Baijiu (LFB) fermentation is a representative spontaneous mixed-culture solid-state fermentation process in which sorghum is used as the raw material. Raw materials and microorganisms are crucial to the flavor formation and quality of LFB. However, the microbial and physicochemical dynamics of different sorghum varieties during LFB fermentation, as well as their impact on flavor compounds are still largely unknown. Herein, PacBio single-molecule real-time (SMRT) sequencing and headspace solid-phase microextraction coupled with gas chromatographymass spectrometry (HS-SPME-GC-MS) were applied to investigate microbial community succession and volatile flavor formation in glutinous/non-glutinous sorghum-based fermented grains during LFB fermentation. Fermented grains made of glutinous sorghum Liangnuo No. 1 (GLN) had higher bacterial α-diversity and lower fungal α-diversity than those with fermented grains prepared with non-glutinous red sorghum (NRS) (p < 0.05). The dominant microbial species were Saccharomyces cerevisiae, Acetobacter pasteurinus, and Lactobacillus helveticus, the latter two of which were the predominant bacteria observed at the end of fermentation in GLN and NRS, respectively. Moisture content and reducing sugar had a more significant impact on the microorganisms in GLN, while amino acid nitrogen, total free amino acids, and residual starch were the main driving factors driving the microbial community in NRS. The correlation network and discriminant analysis indicated that a relatively high content of 4-vinylguaiacol showed a significant positive association with significant differential microbial species in GLN. These results provided valuable insights for improving the quality of LFB.